Design Of 0.13-Μm Cmos 3-Stage Cascode DcDc Buck Converter For Battery Operated Devices - Eric Chew, Choon Yean (2017)
As technology advances, voltage supply for on-chip circuit decreases. An example of this is the limited 1 V voltage supply for most 90-nm circuit design. However, even a single lithium ion battery cell used in today’s electronic devices has a nominal voltage of 3.7 V and can even reach 4.2 V during full charge. Therefore, a DC/DC buck down converter that is capable of providing stable voltage and current supplies to the circuits is needed. This research is on the design of a 0.13-μm CMOS with non-high power transistors on-chip buck down converter capable of down converting 3.4 V – 4.2 V to 1 V. The challenge in implementing this design was the used of non-high power transistors which do not have the capability to withstand high voltage and high current but instead have high resistances, as compared to power transistors which are commonly implemented in commercial converter circuits. The design of the buck down converter in this research was based on Continuous Conduction Mode (CCM) to obtain lower noise and better efficiency for high current draw circuits. In addition, the transistors in the power stage of the converter circuit are in stack/cascode configuration in order to utilize a supply voltage of higher than the transistor’s breakdown voltage. Simulation was performed using Cadence SpectreRF. The results show that the designed buck converter with non-high powered transistors is able to function as effectively as its high-powered counterparts with output voltage ripple of less than 5% and capable of delivering up to 500 mA of output current with maximum efficiency of 47.7%. It also achieves a conversion ratio of 0.238, comparable with the existing referenced design.